PERCEIVED STRESSOR AMONG MALAYSIAN STUDENT - Rosni, Nurliyana Md; Isa, Khairunesa; Jamin, Johanisma; Ahmad, Muhammad Fazrulhelmi; Palpanadan, Sarala Thulasi (International Journal of Psychosocial Rehabilitation, 2020)
Stress that can arise from various academic and environmental aspects are very common among university students. Uncontrollable stress level lowers academic, social, psychological, and physical adjustment. This study was conducted to examine the perceived stressor that students faced during their stay at the university. This quantitative study employed random sampling by collecting data from 280 students at a Malaysian University. The self-developed questionnaire was distributed using Google form through students’ email. The data were analyzed with the help of descriptive and inferential statistical techniques. The results obtained were analyzed using SPSS version 26.0. The findings indicated that majority of the Malaysian students experienced a moderate level of academic and environmental stress. This study contributes a lot on assessing the level of stress and identifying the most stressful situation related to academic, personal and environmental factors.